A study of the ionospheric disturbances associated with strong earthquakes using the empirical orthogonal function analysis. (March 2019) - Liu, Jing; Wan, Weixing; Zhou, Chen; Zhang, Xuemin; Liu, Yi; Shen, Xuhui
Highlights: Using EOF method to extract ionospheric disturbances for earthquakes. 10 earthquakes among 16 Ms  ≥ 8.0 earthquakes had ionospheric disturbances. Abnormities were more obvious 5 days before the earthquakes. Using ionospheric electric field and the SAMI2 model to do the simulation study. Electric field direction affects the location of positive and negative abnormities. Abstract: In this study, an ionospheric logTEC model has been constructed using an empirical orthogonal function (EOF) decomposition method. The main orders (1–9 orders) of this EOF model represent the ionospheric background, while the rest high orders represent ionospheric TEC perturbations. Based on this model, logTEC data during 16 Ms  ≥ 8.0 earthquakes from 2000 to 2012 have been analyzed. We found that ionospheric disturbances occurred in 10 earthquakes. Ionospheric abnormities were clearly observed 5 days before the earthquakes, but ionospheric disturbances can also be seen 1 day before, and 1 day and 2 days after the earthquakes. For the TEC data, the possibility of positive (enhanced TEC) and negative (decreased TEC) abnormities is almost the same. Furthermore, by using the simulation results of ionospheric electric field and SAMI2 model, we show that an abnormal westward electric field can lead to electron density enhancements equatorward and decrease polarward of the epicenters, and vice versa for an eastward abnormal electric field.